The promotion of healthy lifestyles: ¿Reality or utopía? - Becoña Iglesias, Elisardo (1999)
Health promotion is a prioritary topic in health psychology. It refers to the development and improvement of behaviors and life styles leading to achieve a healthy life. There is a clear relationship between people's hehavior and general health state. Life style and life quality determines how is the person in terms of health. Definitely there are habits acquired by the urban life style, that are harmful for health both physically and psychologically. In the present study, healthy life are studied based on scientific findings.